Photocatalytic Reduction of CO2 With Solvent on Alumina Supported With Tio2 - Mohd Hatim Helmi, Mohd Zahariman (2013)
Carbon dioxide accounts for the largest share of the world’s greenhouse gas emissions. There is a growing need to mitigate CO2 emissions. One of the strategies to mitigate CO2 emissions is using CO2 as a raw material in chemical processes. Reactions involving CO2 typically required high energy input and energy substrate. One of the best routes to reduce CO2 is to transform it to hydrocarbons via photo reduction method. Before that, the methods of preparing catalyst such as sol-gel method and hydrothermal method were studied. Addition of metal oxide such as alumina to TiO2 will changed the distribution of electrons and they prevented the electron hole recombination, thereby enhancing the photo catalytic efficiency in production of methanol. Therefore, hydrothermal method is expected give higher performances of catalyst compared to Sol Gel method. In addition, the effect of catalyst dosage for photo reduction process will be studied. The variety dosages of Al2O3-TiO2 catalyst used are0.5 g, 1.0 g, 1.5g and 2.0 g. The period of reaction for each catalyst dosage is 6 hours which the sample is withdrawn for every 1 hour. Lastly, the sample of methanol is analysed using HPLC.